2006
DOI: 10.1007/s10519-006-9075-6
|View full text |Cite
|
Sign up to set email alerts
|

A Cholinergic Receptor Gene (CHRM2) Affects Event-related Oscillations

Abstract: We report genetic linkage and association findings which implicate the gene encoding the muscarinic acetylcholine receptor M2 (CHRM2) in the modulation of a scalp-recorded electrophysiological phenotype. The P3 (P300) response was evoked using a three-stimulus visual oddball paradigm and a phenotype that relates to the energy in the theta band (4-5 Hz) was analyzed. Studies have shown that similar electrophysiological measures represent cognitive correlates of attention, working memory, and response selection;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 95 publications
1
80
0
Order By: Relevance
“…In healthy subjects genetics also contributes to brain responses, since the theta band energy seen in P300 experiments is related to cholinergic receptor gene (Jones et al 2006), and human nicotinic receptor gene modulates auditory and visual event related potentials (Espeseth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects genetics also contributes to brain responses, since the theta band energy seen in P300 experiments is related to cholinergic receptor gene (Jones et al 2006), and human nicotinic receptor gene modulates auditory and visual event related potentials (Espeseth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…M1 receptor agonists (AF102B, AF150(S) and AF267B-1) which increase synaptic ACh levels are related to improved cognition in various animal Alzheimer's disease models (Fisher et al 2002) and antagonists of presynaptic M2 receptors (which decrease ACh) enhance cognitive ability in rodents and non-human primates (Carey et al 2001). CHRM2 has been shown to be involved in long-term potentiation (Calabresi et al 1998), which is thought to be a fundamental mechanism in learning and memory (Silva 2003), and single nucleotide polymorphisms (SNPs) have been associated with visual evoked brain oscillations suggesting at least a role for CHRM2 in higher mental functioning in humans (Jones et al 2006), although reports that CHRM2 polymorphisms are associated with alcoholism and depression (Comings et al 2002;Edenberg and Foroud 2006;Luo et al 2005;Wang et al 2004) suggest a nonspecific phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that an increase in amplitude and power of Beta waves presents the features of electrophysiological endophenotype in the form of an increased predisposition for addiction to alcohol. It must also be said that this endophenotype is accompanied by disorders of behaviour, already in childhood, and more frequent use of psychoactive substances in adolescence, and more frequent anti-social behaviours and attitudes [48,49,50,51].…”
Section: Alcohol Initiation In Adolescence and Alcohol Addiction In Amentioning
confidence: 99%
“…The scope of these disorders, connected with a decreased P300 amplitude, covers the syndromes of decreased inhibition, abuse of psychoactive substances, distorted and anti-social behaviours, and the Attention Deficit Hyperactivity Disorder (ADHD). In the EEG recordings of individuals addicted to alcohol who are carriers of this gene, the stimulation of cholinergic muscarinic receptors M2 changes the pattern of the recording of slow waves of the delta and theta frequencies, accompanied by the effect of decreased oscillation values induced, which were also considered as endophenotype [49,53].…”
Section: Alcohol Initiation In Adolescence and Alcohol Addiction In Amentioning
confidence: 99%